Rainbow trout (Oncorhynchus mykiss): Potential food products derived from the main aquaculture resource in high Andean regions - Florez-Jalixto, Marco Antonio (2021)
Trout was introduced in our country in 1928 and managed to adapt to the freshwater ecosystems of the Peruvian highlands. It currently represents the economic livelihood of many micro and small-scale fish farmers, together with medium and large companies in regions such as Puno, Pasco, Huancavelica and Junín, whose growth in recent years has been considerable. The 71.98% of this resource was destined for consumption in its fresh state and only 28.02% was processed as frozen, which shows the lack of diversification of value-added products in the production chain of this sweet aquaculture species, together with a shortage of research. Therefore, the purpose of this research was to compile the latest studies, carried out in different countries, related to the processing of this species because it is an excellent raw material due to its nutritional value and techno-functional characteristics. The research work collected covered the use of traditional methods and technologies such as marinating, salting, drying, and smoking, as well as innovative restructuring processes applied to trout minced muscle and filleting by-products. These investigations found that the different food products were differentiated by their physical and sensory attributes, techno-functional properties, shelf life and/or preparation. With this review, we hope to contribute to the triple helix model focused on this resource, from and for the Andes, to promote its sustained production, productive chain, and food security for the inhabitants of the Andean regions.